2006
DOI: 10.1016/j.molcel.2006.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Site Regulation of MDM2 E3-Ubiquitin Ligase Activity

Abstract: The control of p53 ubiquitination by MDM2 provides a model system to define how an E3-ligase functions on a conformationally flexible substrate. The mechanism of MDM2-mediated ubiquitination of p53 has been analyzed by deconstructing, in vitro, the MDM2-dependent ubiquitination reaction. Surprisingly, ligands binding to the hydrophobic cleft of MDM2 do not inhibit its E3-ligase function. However, peptides from within the DNA binding domain of p53 that bind the acid domain of MDM2 inhibit ubiquitination of p53,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
243
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(260 citation statements)
references
References 26 publications
16
243
1
Order By: Relevance
“…3B). Interestingly, even though the BRET 50 does not change much, there is still a specific BRET at 30 µM, indicating that p53 and HDM2 still interact, presumably through the reported second interface site [10].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…3B). Interestingly, even though the BRET 50 does not change much, there is still a specific BRET at 30 µM, indicating that p53 and HDM2 still interact, presumably through the reported second interface site [10].…”
Section: Resultsmentioning
confidence: 94%
“…It has been reported that p53-HDM2 consists of two interfaces [10]. The first is the well-known N-termini target for Nutlin-3 in which the Box I domain of p53 fits into a hydrophobic pocket of HDM2.…”
Section: Discussionmentioning
confidence: 99%
“…MDM2 recognizes a short region in the TA domain of p53 and interferes with its transcriptional activity; at the same time, MDM2 interacts with the DBD region and ubiquitinates p53, promoting its proteasomal degradation. 33,34 As MDM2 is a transcriptional target of p53, inhibition by MDM2 is part of a negative feedback loop on p53 activation. 34 In addition to MDM2, p53 is also bound and regulated by the MDM2-related protein MDMX (also named MDM4).…”
Section: Mdm2mentioning
confidence: 99%
“…Together, these observations suggest subtle but significant differences in the structure and regulation of p53-MDM2 and p53-MDM4 interfaces. Furthermore, recent studies have indicated a more complex regulation for p53-MDM2 interactions: the binding of the N-terminal domain of MDM2 with p53 BoxI may promote conformational changes in MDM2 to stabilize interaction of the MDM2 acidic domain with the p53 DNA binding domain (in a p53 region comprising β-sheets S9-S10 and the conserved BoxV; Wallace et al, 2006). Whether or not the MDM4 acidic region may also interact with the p53 DNA binding domain is presently unknown.…”
Section: Protein Structuresmentioning
confidence: 99%